Conceptualizing "Advertising Text" in the Vietnamese Language and Literature Program for Upper-secondary Students - Nguyen, Can Duc; Le, Tan Thoi (VNU Journal of Science: Education Research, 2017)
This article attempts to reveal the awkwardness and limitations encountered by the textbook writer in writing the lesson on "Composing advertising texts" in Grade 10 Vietnamese Language and Literature program. The analysis of the lesson leads to a preliminary conclusion that the introduction of "Composing advertising texts" to the textbook is irrelevant to real life. This article argues that advertizing is a large social domain, so the introduction of "Composing advertising texts" to the program is truly burdensome if not redundant.